2021
DOI: 10.1038/s41598-021-92001-9
|View full text |Cite
|
Sign up to set email alerts
|

Helminth derived factors inhibit neutrophil extracellular trap formation and inflammation in bacterial peritonitis

Abstract: Despite their protective antimicrobial function, neutrophil extracellular traps (NETs) have been implicated in propagation of inflammatory responses in several disease conditions including sepsis. Highly diffusible exogenous ROS produced under such inflammatory conditions, can induce exuberant NETs, thus making inhibition of NETs desirable in inflammatory diseases. Here we report that helminth parasite excretory/secretory factors termed as parasitic ligands (PL) inhibit ROS-induced NETs by blocking the activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…Hookworms express several antioxidant enzymes, such as SODs, which could interfere with the process of NET formation (Figure 1). Interestingly, extracts of the tapeworm Mesocestoides corti were shown to block the formation of stress‐induced NETs 53 . In this study, parasite products were co‐cultured with neutrophils in the presence of H 2 O 2 , and a reduction in NETs was observed.…”
Section: Neutrophils and Hookworm's Excretory/secretory Products: A S...mentioning
confidence: 72%
See 2 more Smart Citations
“…Hookworms express several antioxidant enzymes, such as SODs, which could interfere with the process of NET formation (Figure 1). Interestingly, extracts of the tapeworm Mesocestoides corti were shown to block the formation of stress‐induced NETs 53 . In this study, parasite products were co‐cultured with neutrophils in the presence of H 2 O 2 , and a reduction in NETs was observed.…”
Section: Neutrophils and Hookworm's Excretory/secretory Products: A S...mentioning
confidence: 72%
“…Interestingly, extracts of the tapeworm Mesocestoides corti were shown to block the formation of stress‐induced NETs. 53 In this study, parasite products were co‐cultured with neutrophils in the presence of H 2 O 2 , and a reduction in NETs was observed. The authors then further determined that ES products block the Transient Receptor Potential Cation Channel Subfamily M Member 2 (TRPM2) as well as downstream autophagy pathways.…”
Section: Neutrophils and Hookworm's Excretory/secretory Products: A S...mentioning
confidence: 76%
See 1 more Smart Citation
“…On the other hand, Schistosome infection relates to an immense oxidative stress by the host that is not sufficient to control infection [ 49 ]. Further data demonstrated that excretory/secretory factors from Mesocestoides corti inhibit ROS-induced neutrophil extracellular traps, showing that the parasite could use this mechanism to attenuate the effects induced by ROS [ 50 ]. It should be highlighted, however, that although oxidative mechanisms are induced by helminth parasite infections, their detrimental role in the parasite itself as well as in the host surroundings is not well-established yet [ 51 , 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, Bouchery et al, showed that NETs released following an N. brasiliensis challenge can directly impair larval viability and the parasites combat this response by secreting DNAse II (123). The ability of helminthderived products to inhibit NET formation was also shown by Chauhan et al that demonstrated that Mesocestoides corti ES products were sufficient to inhibit NET formation in the context of bacterial peritonitis (131). Moreover, it was reported that neutrophils and eosinophils require myeloperoxidase and major basic protein to kill S. stercoralis larvae in vitro (93).…”
Section: The Contributions Of Neutrophils To Antihelminth Immunitymentioning
confidence: 94%